Evaluation of genotoxicity of general anesthesia maintained with desflurane in patients under minor surgery. (8th April 2016) - Nogueira, Flávia R.; Braz, Leandro G.; de Andrade, Leonardo R.; de Carvalho, Ana Lygia R.; Vane, Luiz A.; Módolo, Norma Sueli P.; Aun, Aline G.; Souza, Kátina M.; Braz, José Reinaldo C.; Braz, Mariana G.
Abstract : There is controversy over the genotoxic effects of volatile anesthetics. The available literature on the genotoxicity of desflurane, one of the newest volatile halogenated agents used for general anesthesia maintenance, is scarce. This study aimed to evaluate the genotoxic potential of desflurane in 15 patients without comorbidities, of both sexes, who underwent minor surgeries lasting at least 90 min. Patients enrolled in the study received desflurane anesthesia (6%); blood samples were collected before anesthesia induction (T0), 90 min after the beginning of anesthesia (T1), and on the day following surgery (T2). DNA damage was evaluated in lymphocytes using the alkaline comet assay. We found statistically significant increases in DNA damage in T2 samples compared to T0. The findings suggest that desflurane anesthesia induces DNA strand breaks/alkali‐labile sites on the day after minimally invasive surgery in healthy patients. Environ. Mol. Mutagen. 57:312–316, 2016. © 2016 Wiley Periodicals, Inc.